Fish stock losses due to extreme floods – findings from pond‐based aquaculture in the Czech Republic. Issue 3 (8th December 2017) - Rutkayová, J.; Vácha, F.; Maršálek, M.; Beneš, K.; Civišová, H.; Horká, P.; Petrášková, E.; Rost, M.; Šulista, M.
Abstract : Global climate changes exhibit increasingly severe weather effects throughout Europe, which can affect agriculture by extreme flood events. Those events are related to pond‐based aquaculture damages, which lead to losses of fish stock. The objective was to examine the loss of fish in pond‐based aquaculture during extreme floods in 2002, 2006, 2009, and 2013 in the Czech Republic. The total assessed loss of fish in pond aquacultures caused by recent extreme flood events was 54.2%. The most numerous losses of fish were not achieved in 2002 of extreme events in contrast to logical assumption. Based on the statistical evaluation, carp is significantly ( P < 0.001) less vulnerable (or susceptible to losses) than tench, grass carp, pike, and perch. The study revealed differences between the reactions of diverse fish species to flooding and different susceptibilities to flooding within groups of juvenile and adult fish when considering fish species and their age category. This study summarizes the knowledge about the losses of fish stock in pond‐based aquaculture and exposes pilot findings about the species sensitivity and loss rate during flood events. The outcomes also evaluate flood impacts on different aquaculture companies at the same time, and help them to deal with flood risk management.